Guideline‐Directed Medical Therapy After Hospitalization for Acute Heart Failure: Insights From the CONNECT‐HF - Satoshi Shoji; Lisa Kaltenbach; Bradi B. Granger; Gregg C. Fonarow; Hussein R. Al‐Khalidi; Nancy M. Albert; Javed Butler; Larry A. Allen; David E. Lanfear; Jennifer T. Thibodeau; Brittany M. Chapman; Sandra M. Oliver‐McNeil; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Significant gap remains in the implementation of guideline‐directed medical therapy (GDMT) in patients with heart failure after a hospitalization. We aimed to evaluate the use and titration of GDMT at discharge and over a 12‐month period after hospital discharge and to identify factors associated with GDMT use and titration. Methods and Results The CONNECT‐HF (Care Optimization Through Patient and Hospital Engagement Clinical Trial for Heart Failure) trial evaluated the effect of a hospital and postdischarge quality improvement intervention in participants with heart failure with reduced ejection fraction. In this secondary analysis, we examined use and titration to at least 50% of the target dose of GDMTs at hospital discharge and over time. Among 4646 participants (mean age 63 years, 34% women), GDMT use did not numerically improve from discharge to 12 months: beta blockers (84%–78%), angiotensin‐converting enzyme inhibitors/angiotensin II receptor blockers/angiotensin receptor‐neprilysin inhibitors (73%–65%), mineralocorticoid receptor antagonists (39%–36%), and sodium‐glucose cotransporter 2 inhibitors (1.5%–2.1%). Achieving ≥50% of the target dose also showed little change over 12 months: beta blockers (35%–32%), angiotensin‐converting enzyme inhibitors/angiotensin II receptor blockers/angiotensin receptor‐neprilysin inhibitors (28%–25%). For all medications, use of GDMT at discharge was associated with the use and achieving ≥50% of the target dose at 12 months. Conclusions Following a hospitalization for heart failure, GDMT use remained low and did not numerically improve over 12 months. Use of GDMT at discharge was significantly associated with the use of GDMT over time, highlighting the importance of initiating GDMT during hospitalization.